Persekutuan Dalam Perspektif Biblis-Kristiani - Silvester Manca (Jurnal Alternatif Wacana Ilmiah Interkultural, 2019)
Communion is a theological idea that have very deep and deep roots the Christian Bible, which are later reflected more mature in the living pilgrimage oh the Church. In the bible is stated, both implicitly and explicitly that communion is the essence and mission of God. It is also explained that multidimentional felleowship is a basic human call and the antitthesis sin.